Review on Zakat Core Principles (ZCP) Literatures - Anwar Adem Shikur; Siti Maysyaroh (SMART Insight, 2023)
This research aims to map research related to the zakat core principle that has been published in journals indexed in Dimensions from 2016 to 2023. The method used in this study is a qualitative approach with the support of NVivo software. The results of this study reveal that cluster analysis also explains research lines that include aspects such as zakat management, zakat technology, and zakat governance. These findings provide in-depth insight into the various perspectives and issues that exist in the zakat core principle literature. The implication of this research is that zakat management, the application of technology in zakat management, and effective governance in zakat institutions have a crucial role in implementing the core principles of zakat. These results can be a basis for better understanding the complexity of zakat core principles and contribute to improving zakat management practices by considering various relevant perspectives and aspects.